Historic Documentation of the Monroe Street Bridge, Spokane County, Washington, - Gough, Stan
Eighteen page report by the Archaeological and Historical Services, Eastern Washington University entitled "Historic Documentation of the Monroe Street Bridge, Spokane County, Washington," by Susan Axton and Stephen Emerson; Principal Investigator: Stan Gough. This was short report #717 for the City of Spokane dated May 2002. The report includes photographs and negatives, which are indexed.